Hubungan Peran Orang Tua Dengan Motivasi Belajar Biologi Peserta Didik Kelas XI Di SMA Negeri 7 Padang - Yuni Sartika; Ristiono Ristiono (JURNAL PENDIDIKAN ROKANIA, 2022)
This study aims to determine the relationship between the role of parents and the motivation to learn Biology of Class XI students at SMA Negeri 7 Padang, how much contribution is made and the results are significant or not. This research was conducted on June 20, 2022 – August 31, 2022 2022. The sample is 50 in one class. The sampling technique is proportional random sampling or a balanced sample. In this study, samples were taken with a total of 25% of the total population. The data in this study were analyzed using a simple Pearson Product Moment correlation formula, then a t-test was performed to determine whether or not the relationship was significant. The method used in this research is descriptive quantitative method. The data obtained were analyzed using techniques. The research instrument used was a questionnaire in the form of a table. This method was chosen because it is in accordance with the research objectives to be achieved. The results showed that there was a correlation between the role of parents and the motivation to learn. The results showed that the role of parents was 86.75% with very good criteria. Learning motivation is 88.29% with very good criteria. The value of r = 0.263 coefficient t_count is 2.465> 2.00, so it can be concluded that there is a significant and positive relationship between the role of parents and the motivation to learn Biology of Class XI students at SMA Negeri 7 Padang.